Penerapan Metode Targeted Sequencing pada Penyakit Kanker - Latif, Rahmawati; Hala, Yusminah (BEST Journal (Biology Education, Sains and Technology), 2024)
The purpose of this study is to examine the application of the Targeted Sequencing method for various types of cancer. This research uses a literature review method, involving the collection, analysis, and synthesis of relevant scientific sources to answer the research question. The results of the study, based on the literature approach, indicate that Targeted Sequencing is an alternative for detecting and identifying cancer, making it easier to determine appropriate treatments and therapies. Targeted Sequencing has significant potential in the personalization of cancer treatment. However, challenges such as tumor heterogeneity, panel limitations, high costs, and clinical validation need to be addressed to ensure maximum benefits for patients. Collaboration among genomic experts, clinicians, and researchers is necessary to overcome these obstacles.